Nitrogen fertilization on palisadegrass: phytomass decomposition and nutrients release - Costa, Claudio Hideo Martins Da; Crusciol, Carlos Alexandre Costa; Soratto, Rogério Peres; Ferrari Neto, Jayme; Moro, Edemar (Escola de Agronomia/UFG, 2016)
ABSTRACT Topdressing or pre-seeding nitrogen (N) application increases phytomass production, providing a higher nutrients accumulation and indirectly favoring the subsequent crop. However, N fertilization can alter the dry matter decomposition and nutrients release dynamics. This study aimed at evaluating the decomposition rate, cellulose, lignin and nutrients release speed from palisadegrass as a function of N fertilization. The experimental design was randomized blocks with four replications, in a factorial scheme constituted by two N fertilization levels and six sampling times after desiccation [0, 14, 34, 41, 51 and 68 days after management (DAM)]. The topdressing N fertilization on palisadegrass increases the dry matter production and N accumulation, but does not alter the decomposition and release speed. N fertilization reduces the C/N ratio, but it does not change the contents of cellulose and lignin and the decomposition and release of N, K, Ca, Mg, C and Si. The amounts of P and S accumulated in the plant and released into the soil increase with N fertilization. The maximum release rates occur within 0-14 DAM, being more intensive for P and S when N is applied. These results demonstrate the high potential of this species for crop-livestock integration systems, with some advantages that can be potentialized with higher N doses.

RESUMO A aplicação de nitrogênio (N) em cobertura ou pré-semeadura aumenta a produção de fitomassa, gerando maior acúmulo de nutrientes e favorecendo indiretamente a cultura em sucessão. Contudo, a adubação com N pode alterar a decomposição e a dinâmica de nutrientes da fitomassa. Objetivou-se avaliar a taxa de decomposição, celulose e lignina e velocidade de liberação de nutrientes da fitomassa do braquiarão, em função da aplicação de N. O delineamento experimental foi em blocos casualizados, com quatro repetições, em esquema fatorial constituído por dois níveis de adubação nitrogenada e seis épocas de coleta após dessecação [0, 14, 34, 41, 51 e 68 dias após o manejo (DAM)]. A aplicação de N em cobertura no braquiarão aumenta a produção de matéria seca e o acúmulo de N, mas não altera a velocidade de decomposição e liberação. A adubação nitrogenada reduz a relação C/N, porém, não altera os teores de celulose, lignina e a decomposição e liberação de N, K, Ca, Mg, C e Si. A quantidade de P e S acumulada na planta e liberada para o solo aumenta com a adubação nitrogenada. As máximas taxas de liberação ocorrem no período de 0-14 DAM, de forma mais intensa para o P e S quando o N é aplicado. Esses resultados evidenciam o elevado potencial dessa espécie para sistemas de integração lavoura-pecuária, com algumas vantagens que podem ser potencializadas com doses maiores de N.
Adubação nitrogenada em braquiarão: decomposição da fitomassa e liberação de nutrientes
Keywords: Urochloa brizantha; cellulose; lignin; straw persistence; nutrients recycling; Urochloa brizantha; celulose; lignina; persistência de palhada; reciclagem de nutrientes